Enhancing Extracellular Adenosine Levels Restores Barrier Function in Acute Lung Injury Through Expression of Focal Adhesion Proteins - Wang, Wei; Chen, Ning-yuan; Ren, Dewei; Davies, Jonathan; Philip, Kemly; Eltzschig, Holger K.; Blackburn, Michael R.; Akkanti, Bindu; Karmouty-Quintana, Harry; Weng, Tingting (Frontiers in Molecular Biosciences, 2021)
Background: Acute respiratory distress syndrome (ARDS) is a clinical presentation of acute lung injury (ALI) with often fatal lung complication. Adenosine, a nucleoside generated following cellular stress provides protective effects in acute injury. The levels of extracellular adenosine can be depleted by equilibrative nucleoside transporters (ENTs). ENT inhibition by pharmaceutical agent dipyridamole promotes extracellular adenosine accumulation and is protective in ARDS. However, the therapeutic potential of dipyridamole in acute lung injury has not yet been evaluated. Methods: Dipyridamole, epithelial specific ENT2 or adenosine A2B receptor (Adora2b) deficient mice were used to study their effects in bleomycin-induced ALI. MLE12 cells were used to probe downstream Adora2b signaling. Adenosine receptors, transporters, and targets were determined in ARDS lungs. Results: ENT2 is mainly expressed in alveolar epithelial cells (AEC) and is negatively regulated by hypoxia following tissue injury. Enhancing adenosine levels with ENT1/ENT2 inhibitor dipyridamole at a time when bleomycin-induced ALI was present, reduced further injury. Mice pretreated with the ADORA2B agonist BAY 60-6583 were protected from bleomycin-induced ALI by reducing vascular leakage (558.6 ±50.4 vs 379.9 ± 70.4, P<0.05), total bronchoalveolar lavage fluid (BAL) cell numbers (17.9 ± 1.8 to 13.4 ± 1.4 e4, P<0.05), and neutrophil infiltration (6.42 ± 0.25 vs 3.94 ± 0.29, P<0.05). While mice lacking Adora2b in AECs were no longer protected by dipyridamole. We also identified occludin and focal adhesion kinase (FAK) as downstream targets of Adora2b, thus providing a novel mechanism for adenosine-mediated barrier protection. Similarly, we also observed similar enhanced ADORA2B (3.33 ± 0.67 to 16.12 ± 5.89, P<0.05) and decreased occludin (81.2 ± 0.3 to 13.3 ± 0.4, P<0.05) levels in human ARDS lungs. Conclusions: We have highlighted a role of dipyridamole and adenosine signaling in preventing or treating ALI and identified Ent2 and Adora2b as key mediators in important for the resolution of ALI.